Pengaruh Moderating Ukuran Bank dan Faktor-Faktor Financial Distress Terhadap Kinerja Keuangan - Risa Febriana Putri; Suci Atiningsih (Universitas Muhammadiyah Palembang, 2025)
This study aims to empirically test the moderating effect of bank size and financial distress factors on financial performance in the conventional banking sector listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. This study had the population of 43 conventional banks, but only 40 conventional banks met the research criteria. With a five-year observation period, the total observation data was 200. After removing outliers, the final sample size was 100. The sampling tehnique used is the purposive sampling tehnique. This study employed a quantitative approach, utilizing from EVIEWS 12 application data. The results of this study indicate that liquidity has a positive effect on financial performance, asset quality has a positive effect on financial performance, CAR has no effect on financial performance. Bank size, as a moderating variable, can strengthen liquidity's impact on financial performance. Bank size, as a moderating variable, strengthens asset quality's impact on financial performance. Bank size, as a moderating variable, weakens CAR's impact on financial performance.